Current Principles in the Management of a Mangled Hand - Martina Macrì, MD; Pierfrancesco Pugliese, MD; Graziano Accardo, MD; Alice Clemente, MD; Valentina Cecconato, MD; Simona Odella, MD; Pierluigi Tos, MD, PhD (Journal of Hand Surgery Global Online)
Mangled upper-extremity injuries can have devastating consequences for the patient. The goal of treatment was to recreate a functional hand with a minimum of three sensitive and opposable fingers to achieve an acceptable quality of life. Early management of injuries is critical to treatment success. Initial assessment begins in the emergency department where the injury is quantified and the amputated segments are evaluated, particularly the possibility of replanting them or using them as spare parts as tissue bank. In the operating room, careful debridement is essential for any reconstruction. Despite advances in reconstructive techniques, the management of these injuries is a challenge for the surgeon. The main treatment guidelines and a step-by-step approach to the mangled hand are presented to achieve acceptable results.